Differential Development of Professional Knowledge and Problem-Solving Skills During VET: The Role of Cognitive Resources, School-Leaving Certificates, and Sociodemographic Background - Jennifer Schauer; Stephan Abele; Julian M. Etzel (Vocations and Learning, 2025)
In this study, we investigated the development of apprentices' professional knowledge and problem-solving skills during the second half of dual vocational education and training (VET). We analyzed (1) the average level of development, (2) interindividual differences in this development, and (3) the effects of cognitive resources, school-leaving certificates, and sociodemographic background as covariates of the development. Professional knowledge (n0.167em=0.167em473) and problem-solving skills (n0.167em=0.167em322) were assessed towards the end of the second (T1) and third year (T2) of VET. Using latent change score analyses, we found (1) an average increase in professional knowledge, (2) substantial variance in change, and (3) associations between the apprentices' change and their cognitive resources (specifically, fluid intelligence and the prior level of professional knowledge). Beyond that, there were no effects of school-leaving certificates, socioeconomic status and migration background on the change between T1 and T2 but we found these covariates to be partly associated with the apprentices' prior level of professional knowledge at T1. As we detected large estimation uncertainties in the results for problem-solving skills, no reliable interpretation was possible for this outcome. In sum, our study reveals inconclusive findings on the effectiveness of VET programs in promoting learning and, at the same time, emphasizes the large heterogeneity in learning trajectories that needs to be accounted for in VET practice to improve success for all apprentices.
Keywords: 370; Development; Latent change score analysis; Problem-solving skills; Professional knowledge; Troubleshooting skills; Vocational education and training (VET)